2019
DOI: 10.1002/pa.1942
|View full text |Cite
|
Sign up to set email alerts
|

Brain drain and South Africa's socioeconomic development: The waves and its effects

Abstract: Many African countries are bedeviled with huge losses of human skills, and this, in turn, has affected thier development. From health professionals to teachers, academics and engineers, the continent has lost numerous skilled personnel who ought to be contributing extensively to its socio‐economic development. The socio‐economic development of a country hinges on the availability of skilled human resources to drive its growth. Brain drain has long being a challenge for South Africa as the country continues to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Many African countries suffer from the loss of their skilled human resources in various fields of science. This has had a terrible impact on the sustainable development of these countries (Mlambo & Adetiba, 2019 ). According to participants, brain drain could be one of the negative aspects of internationalization, especially for low- and middle-income countries.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Many African countries suffer from the loss of their skilled human resources in various fields of science. This has had a terrible impact on the sustainable development of these countries (Mlambo & Adetiba, 2019 ). According to participants, brain drain could be one of the negative aspects of internationalization, especially for low- and middle-income countries.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Capuano and Marfouk (2013), for instance, state that economic indicators in African countries which experience brain drain are not improving; therefore, although investment agencies seek various ways to inspire confidence in their country and give recommendations to investors, they are unable to attract said investors to their countries precisely because of brain drain. Mlambo & Adetiba (2019) and Chimboza (2012) have also called attention to similar findings which indicate that the exodus of medical personnel, teachers, professors, and engineers from North African countries has severely damaged these countries' socio-economic development. In addition, the government's inability to develop effective policies to prevent brain drain has accelerated this process.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 93%
“…All of these factors directly relate to governmental authorities; they do ensure young graduates should not move to the host country for the above-described reasons (Hashmi et al, 2012;Parveen et al, 2022). An empirical study conducted by Bang and Mitra, (2011) also identified that the political institutions should play the role and develop skills among the labor for better productivity and income (Mlambo, V. H., & Adetiba, T. C., 2019). A study revealed that the key problem of brain drain is the economic policy that the existing government hold practically.…”
Section: Empirical Studies Hypothesis Developmentmentioning
confidence: 99%